The Role of Problem Based Learning Learning in Improving Student Character Education - Manurung, Alberth Supriyanto; Halim, Abdul; Rosyid, Ainur (Universitas Pahlawan Tuanku Tambusai, 2023)
The Determine the Role of Problem-Based Learning for Student Character Education was the aim of this study. Simple regression and correlation analysis methods are utilized in the survey-based research methodology. Using the Cluster Sampling approach, this study was carried out at SDN Kenari 07 Pagi in the Salemba District with a total of 36 participants. (1) The role of problem-based learning in student character education; (2) Interest influences problem-based learning implementation; (3) Student background influences problem-based learning implementation; and (4) Intelligence affects problem-based learning implementation. Based on this research, it is anticipated that the influence of problem-based learning will help character education for elementary school kids in the fifth grade, because the outcomes of the verification show that Problem Based Learning plays a significant determining role. In many ways, the character improvement model is used to address educational issues, and one of them is the problem-based learning learning model, which undoubtedly has an impact on children's development because each child has unique traits that can be used to demonstrate the child's character when resolving issues.